2020
DOI: 10.4314/ijbcs.v13i6.26
|View full text |Cite
|
Sign up to set email alerts
|

Diversité biologique et caractérisation de l’activité de maraîchage sur le site de Grand-Popo au Sud Bénin

Abstract: RESUMELe maraîchage revêt une importante source alimentaire et constitue l'une des activités les plus génératrices de revenus au Bénin. La présente étude a pour objectif de contribuer à la sécurité alimentaire à travers une meilleure connaissance des cultures maraîchères de même que les difficultés liées à leur production. Les données ont été collectées à travers des enquêtes individuelles auprès de trente-deux (32) maraîchers installés sur le site maraîcher de Grand-Popo. Au total, neuf (9) espèces maraîchère… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 5 publications
1
2
0
1
Order By: Relevance
“…The present study identified pests and diseases as the major constraints that hinder the development of the snap beans sector in Benin. A similar trend was observed by Adjatin et al ( 19 ), who reported that insects, nematodes and pathogens, including fungi, were severe threats facing vegetable production in Benin. Agoyi et al ( 18 ) demonstrated that in addition to pests and diseases, there need to be more good farming practices for snap beans production in Benin.…”
Section: Discussionsupporting
confidence: 86%
“…The present study identified pests and diseases as the major constraints that hinder the development of the snap beans sector in Benin. A similar trend was observed by Adjatin et al ( 19 ), who reported that insects, nematodes and pathogens, including fungi, were severe threats facing vegetable production in Benin. Agoyi et al ( 18 ) demonstrated that in addition to pests and diseases, there need to be more good farming practices for snap beans production in Benin.…”
Section: Discussionsupporting
confidence: 86%
“…Family labor is the most used 76.21% The present results allowed the identification of twelve ( 12) market gardening species in the different farms surveyed compared to nine (09) market gardening species identified in Grand-Popo in southern Benin by Adjatin et al, (2019).…”
Section: Discussionmentioning
confidence: 75%
“…In Benin, vegetable production is characterized by a diversification of cultivated species (Ahouangninou et al, 2013). The income generated by this market gardening activity allows several hundred families to meet their daily needs (Adjatin et al, 2019).…”
Section: Marcelle-agathe Mondementioning
confidence: 99%
“…Although agriculture is one of the main sectors of activity contributing to the socio-economic development of populations. This sector employs more than 40% of the world's working population, including more than 52% in Africa [4,5]. In the agricultural sector, market garden crops play an important role in human nutrition, and are an effective response to urban food demand [6].…”
Section: Introductionmentioning
confidence: 99%